2014
DOI: 10.1111/hpb.12094
|View full text |Cite
|
Sign up to set email alerts
|

Jaundice: an important, poorly recognized risk factor for diminished survival in patients with adenocarcinoma of the head of the pancreas

Abstract: Preoperative jaundice is a negative risk factor in adenocarcinoma of the pancreas. Additional studies are required to determine the exact mechanism for this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 16 publications
6
42
1
3
Order By: Relevance
“…So, we could not analyze influence of jaundice duration, and a possible benefit of preoperative biliary drainage on early morbidity and late survival. However, is noteworthy that biliary drainage did not compromise long-term survival in the present study as in others (17) or seems even able to improve longterm survival (16).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…So, we could not analyze influence of jaundice duration, and a possible benefit of preoperative biliary drainage on early morbidity and late survival. However, is noteworthy that biliary drainage did not compromise long-term survival in the present study as in others (17) or seems even able to improve longterm survival (16).…”
Section: Discussionsupporting
confidence: 64%
“…However, a recent randomized controlled trial demonstrated that endoscopic biliary stenting should not be used routinely before PD when serum bilirubin level is below 250 µmoles/L because overall morbidity is significantly increased in patients who receive biliary stent while surgery-related complications are not decreased in the stent arm (12). Previous studies have also identified that jaundice negatively influenced long term survival after pancreatic resection for PDAC (13)(14)(15)(16)(17). However, in some studies jaundice per se was deleterious globally (13) or only in a subset of patients (16) whereas in others only severe jaundice according to variable definitions was associated with a decreased survival (14,15,17).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Biliary obstruction and the resulting hyperbilirubinaemia usually complicate the management of patients by increasing the risk of cholangitis and causing frequent hospitalisations [11]; hyperbilirubinaemia has been associated with shorter overall survival in patients with pancreatic cancer [12,13]. Biliary decompression in patients with obstructive hyperbilirubinaemia is commonly performed using endoscopic stent placement [10], which not only reduces morbidity [14] but also facilitates treatment with chemotherapy by allowing total bilirubin levels to drop to ≤ 1.5-2 times the upper limit of normal (≤ 1.5-2 × ULN).…”
Section: Introductionmentioning
confidence: 99%
“…This difference was not statistically significant, but the findings of Strasberg et al 1 have been validated by other groups. 3 Following the approach used by Strasberg et al, 1 we found tumour size, alkaline phosphatase level, tumour-nodemetastasis (TNM) stage, grading and margin status to be significant prognostic factors in univariate analyses. When all factors were entered in a multivariate model, grading and margin status remained significant.…”
mentioning
confidence: 59%